سمو الذات لدى طلبة الجامعة في ضوء بعض المتغيرات - العبيدي, عفراء ابراهيم خليل إسماعيل (Sciences de l'Homme et de la Société; Vol. 18 (2016): SCIENCES DE L'HOMME ET DE LA SOCIÉTÉ)
يهدف البحث الحالي إلى التعرف على سمو الذات لدى طلبة الجامعة  بدلالة الفرق في سمو الذات بحسب متغير الجنس، وقد قامت الباحثة باعداد مقياس سمو الذات لدى طلبة الجامعة وبعد ان تحققت من خصائص المقياس طبقته على عينة بلغت (168) طالباً وطالبة والذين اختيروا بالطريقة العشوائية وقد اظهرت النتائج ان العينة لديها سمو ذات كما بينت النتائج عدم وجود فروق في سمو الذات بين الجنس، وفي ضوء هذه النتائج اوصت الباحثة ببعض التوصيات والمقترحات.   Abstract :         The goal of current research know Self-Transcendence  among university students in terms of the difference in HH self according to the variable sex, The researcher numbers Highness self scale with university students and having achieved the scale properties applied to a sample of (168) students who were selected randomly Experimental results show the sample has Highness with as results showed no differences in Self-Transcendence  between males and females, and in the light of these findings the researcher recommended some of the recommendations and proposals.